Øysand research site: Geotechnical characterisation of deltaic sandy-silty soils - Quinteros,S; Gundersen,A; L'Heureux,JS; Lunne,T; Harb,Carraro JA; Jardine,R (AIMS Geosciences, 2019)
This paper describes the geology and geotechnical engineering properties of the fluvial and 18 deltaic gravelly-sandy-silty sediments at Øysand, Norway. Geophysical and geotechnical site 19 investigations carried out between 2016 and 2018 at the site are presented. Field testing included state-20 of-the-practice and state-of-the-art soil characterisation techniques such as total sounding, seismic 21 cone penetration testing, seismic flat dilatometer, multichannel analysis of surface waves, electrical 22 resistivity tomography, ground penetrating radar, piezometers, thermistors strings, slug tests, and 23 permeability tests using a newly developed CPT permeability probe from NGI. Several sampling 24 techniques were used at the site to assess sample quality. Laboratory testing consisted of index tests 25 and advanced triaxial tests with bender elements to estimate shear strength and stiffness. Data 26 interpretation, engineering soil properties and state variables derived from this analysis are presented, 27 along with comments on data quality. Engineering problems investigated at Øysand so far, are related 28 to: the impact of using different CPTU types, sample quality assessment by obtaining soils with state-29 of-the-practice and state-of-the-art techniques (such as gel push sampler and ground freezing), and 30 frost heave susceptibility.